2001
DOI: 10.1007/s001130170080
|View full text |Cite
|
Sign up to set email alerts
|

Patellametastase eines Kolonkarzinoms

Abstract: Although bone tumors are often located in the knee area, primary tumors of the patella are rare, and patellar metastases extremely rare. Only a few cases were reported in the literature originating from different primary tumors, mostly lung and breast [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 18, 19, 20, 22]. There is only one other case description of a colon carcinoma [21]. We present a rare case of primary sigma carcinoma and patellar metastasis. Because of the increasing rate of colon carcinomas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Metastatic bone tumors rarely occur. There have been reports of metastatic bone tumors from lung cancer, renal cancer, esophageal cancer, colorectal cancer, malignant lymphoma, and malignant melanoma; however, to our knowledge, no study has reported bone tumors as metastasis of gastric cancer [ [7] , [8] , [9] , [10] , [11] ]. Therefore, we thought that patellar bone metastasis was unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastatic bone tumors rarely occur. There have been reports of metastatic bone tumors from lung cancer, renal cancer, esophageal cancer, colorectal cancer, malignant lymphoma, and malignant melanoma; however, to our knowledge, no study has reported bone tumors as metastasis of gastric cancer [ [7] , [8] , [9] , [10] , [11] ]. Therefore, we thought that patellar bone metastasis was unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Others such as osteoid osteomas, intraosseous lipomas, and intraosseous hemangiomas have also been reported [ [4] , [5] , [6] ]. Conversely, metastatic patellar tumors are infrequently reported, with only a few case reports, and primary sites include the lung, kidney, esophageal, malignant melanoma, colon, and head and neck cancer [ [7] , [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%
“…Metastatic colon cancer affecting the patella is exceedingly rare; in fact, during the 20-year period from 1969 to 1989, there were no reported cases in the literature ( 10 ). To our knowledge, there have only been two reported cases of adenocarcinoma of the rectum and two reported cases of adenocarcinoma of the colon that have metastasized to the patella ( 9 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…This inflexibility in the medical encounter leaves already vulnerable patients in an even more handicapped position. Patient attempts to negotiate often result in expressed animosity on the part of health care providers [13]. A setting like this leaves patients thinking they cannot be active participants in their health care.…”
mentioning
confidence: 99%